Conceptualisation of postnatal depression in Malaysia: The contribution of critical realism in exploring the understanding of women’s and healthcare practitioners’ perspectives - Mohd Arifin, Siti Roshaidai; Margaret Maxwell, Helen Cheyne, (Opción)
This study aimed to explore the perception of PND in women and healthcare practitioners (HCPs) in Malaysia using critical realism. This qualitative study was conducted among 33 Malaysian women attending child or postnatal care and 18 healthcare practitioners (HCPs) using face-to-face semi-structured interviews in six selected maternal and child health clinics and a female psychiatric ward in Kuala Lumpur, Malaysia. The findings suggest that the women’s and HCPs’ conceptualisations of PND are not entirely established based on either scientific or professional expertise, indicating that there is a lack of systematic awareness of PND within the Malaysian healthcare setting.